Clinical outcomes of locally advanced esophageal neuroendocrine carcinoma treated with chemoradiotherapy. (3rd December 2019) - Honma, Yoshitaka; Nagashima, Kengo; Hirano, Hidekazu; Shoji, Hirokazu; Iwasa, Satoru; Takashima, Atsuo; Okita, Natsuko; Kato, Ken; Boku, Narikazu; Murakami, Naoya; Inaba, Kouji; Ito, Yoshinori; et al.
Abstract: Background: Neuroendocrine carcinoma (NEC) arising from the esophagus (EsoNEC) is extreme rare, accounting for approximately 1% of esophageal cancer. Even for localized NEC, multidisciplinary approach including chemotherapy is recommended in treatment guidelines because of its high rates of systemic recurrence. However, it is controversial whether adding surgery or radiotherapy is appropriate local treatment for EsoNEC. There have been few reports regarding the clinical outcomes of definitive chemoradiotherapy (dCRT) for EsoNEC. The purpose of this study was to clarify the survival outcome of patients with locally advanced EsoNEC treated with dCRT. Methods: Clinical outcomes, feasibility, and prognostic factors of patients with locally advanced EsoNEC treated with radiotherapy (60 Gy/30 fraction) in combination with platinum plus etoposide (CE‐RT) or cisplatin plus 5‐fluorouracil (CF‐RT) at the National Cancer Center Hospital from 2001 to 2017 were retrospectively analyzed. Results: A total of 22 patients were identified as the subjects of this study. The overall response rate and clinical complete remission rate in all patients were 86.4% and 77.3%, respectively. The median progression‐free survival and median survival time in all patients were 12.7 and 37.5 months, associated with a 5‐year survival rate of 45.4%. Patients treated with CE‐RT experienced more hematological adverse events, especially in neutropenia (≥grade 3) and febrile neutropenia(≥grade 3), but achieved more long‐term progression‐free survival than with CF‐RT. Conclusions: Definitive chemoradiotherapy can be considered as an important treatment option for locally advanced esophageal neuroendocrine carcinoma. Abstract : Definitive chemoradiotherapy can be considered as an important treatment option as well as surgery for locally advanced esophageal neuroendocrine carcinoma.